Suaka dan Hukum Pengungsi Internasional - Maya I Notoprayitno (Jurnal Cita Hukum, 2013)
Asylum and Law for International Refugee. Some criteria have been determined for individual to have refugee status, and the country which grant the asylum would give the status based on social and humanity considerations. Therefore, the issue of granting asylum and refugee status can be seen not only political perspectives but also from juridical perspectives since it has been governed by international law, specifically the law of International Refugee. This article would focus on some cases on how asylum seekers got their refugee status, especially on the case of some Papuans who have obtained their refugee status and temporary visa from the Australian government in 2006. DOI: 10.15408/jch.v1i1.2983